Berry Extracts and Their Bioactive Compounds Mitigate LPS and DNFB-Mediated Dendritic Cell Activation and Induction of Antigen Specific T-Cell Effector Responses - Puja Upadhaya; Felipe F. Lamenza; Suvekshya Shrestha; Peyton Roth; Sushmitha Jagadeesha; Hasan Pracha; Natalie A. Horn; Steve Oghumu (MDPI AG, 2023)
Berries have gained widespread recognition for their abundant natural antioxidant, anti-inflammatory, and immunomodulatory properties. However, there has been limited research conducted thus far to investigate the role of the active constituents of berries in alleviating contact hypersensitivity (CHS), the most prevalent occupational dermatological disease. Our study involved an ex vivo investigation aimed at evaluating the impact of black raspberry extract (BRB-E) and various natural compounds found in berries, such as protocatechuic acid (PCA), proanthocyanidins (PANT), ellagic acid (EA), and kaempferol (KMP), on mitigating the pathogenicity of CHS. We examined the efficacy of these natural compounds on the activation of dendritic cells (DCs) triggered by 2,4-dinitrofluorobenzene (DNFB) and lipopolysaccharide (LPS). Specifically, we measured the expression of activation markers CD40, CD80, CD83, and CD86 and the production of proinflammatory cytokines, including Interleukin (IL)-12, IL-6, TNF-α, and IL-10, to gain further insights. Potential mechanisms through which these phytochemicals could alleviate CHS were also investigated by investigating the role of phospho-ERK. Subsequently, DCs were co-cultured with T-cells specific to the OVA323-339 peptide to examine the specific T-cell effector responses resulting from these interactions. Our findings demonstrated that BRB-E, PCA, PANT, and EA, but not KMP, inhibited phosphorylation of ERK in LPS-activated DCs. At higher doses, EA significantly reduced expression of all the activation markers studied in DNFB- and LPS-stimulated DCs. All compounds tested reduced the level of IL-6 in DNFB-stimulated DCs in Flt3L as well as in GM-CSF-derived DCs. However, levels of IL-12 were reduced by all the tested compounds in LPS-stimulated Flt3L-derived BMDCs. PCA, PANT, EA, and KMP inhibited the activated DC-mediated Interferon (IFN)-γ and IL-17 production by T-cells. Interestingly, PANT, EA, and KMP significantly reduced T-cell proliferation and the associated IL-2 production. Our study provides evidence for differential effects of berry extracts and natural compounds on DNFB and LPS-activated DCs revealing potential novel approaches for mitigating CHS.